Numerical study of effect of fluke inclination on behavior of drag anchor in clay with linearly increasing shear strength under unidirectional and combined loading. (October 2019) - Wu, Xiaoni; Chow, Yean Khow; Leung, Chun Fai
Highlights: An in-depth study of drag anchor behavior in clay with linearly increasing shear strength under unidirectional and combined loading. The effects of the practical fluke inclination angle and soil non-homogeneity, on the capacity and anchor failure mechanism are investigated. The effects of anchor embedment depth ratio and interface condition are investigated. The effects of the fluke inclination angle and soil non-homogeneity on the yield envelopes for different anchor behavior are studied. Yield envelope functions for different anchor positions are provided. Abstract: Drag anchor is a widely used anchor type in offshore engineering for the mooring system. The prediction of the anchor trajectory installation and the final position is important for anchor selection in design. The existing method using yield envelope method for trajectory prediction ignored the shallow anchor behavior but applied the deep yield envelope from a deeply embedded horizontal fluke in uniform clay for the whole drag-in installation process. However, the anchor fluke embedment depth and inclination angle change continually during installation in clay with linearly increasing shear strength soil profile in practice. Studies on the effect of fluke inclination angle on the anchor behavior in clay with such non-uniform soil profile under unidirectional and combined loading are important and necessary for the improvement of the yield envelope method to ensure a reasonable prediction. The current 2D finite element studies investigate the anchor behavior for inclined fluke in clay with linearly increasing shear strength under unidirectional vertical, horizontal and rotational loadings first. Then the effects of the fluke inclination angle, soil non-homogeneity and embedment depth ratio on the shallow yield envelopes are investigated. It is found that the effect of fluke inclination angle on the vertical capacity factors for anchor in clay with non-uniform and uniform soil profile is largely different. The resultant large impact on the yield envelopes shown here illustrates the importance of considering the fluke inclination angle and soil non-homogeneity in the prediction of anchor trajectory using yield envelope method.